STORING ELECTRONIC RECEIPTS ON A REMOVABLE STORAGE MEDIUM (2002)
본 발명은 전자 영수증을 사용하여 상품 및 서비스에 대한 거래를 부호화하는 방법 및 장치를 제공한다. 고객 및 상인은 분산 데이터 처리 시스템을 사용하여 상거래를 수행한다. 전자 영수증은 제1 데이터 처리 시스템에 있는 소거 가능 저장 매체 상에 기록된다. 상기 전자 영수증은 상기 상거래에 관련된 데이터를 포함한다. 이어서, 상기 소거 가능 저장 매체가 제2 데이터 처리 시스템에서 판독된다. 상기 전자 영수증을 확인한 후에, 다른 상거래 또는 최초 상거래의 다른 단계가 수행될 수 있다. 상기 전자 영수증은 상기 구매 거래로 인한 상품 또는 서비스에 대한 보증 요청이 있는 경우에 확인될 수 있고, 상기 소거 가능 저장 매체에는 광학 카드 또는 스마트 카드가 있으며, 어떤 것이든 전자 서명, 디지털 인증서 등을 통해 각각 보증된 무결성을 갖는 수많은 상거래 관련 전자 영수증 및 기타의 전자 문서를 저장할 수 있다. A method and apparatus for encoding transactions for goods and services using an e-receipt is provided. A consumer and a merchant conduct a commercial transaction using a distributed data processing system. An electronic receipt is recorded on a removable storage medium at a first data processing system. The electronic receipt contains data concerning the commercial transaction. The removable storage medium is then read at a second data processing system. After validating the electronic receipt, another commercial transaction or another stage of the original commercial transaction may be performed. The electronic receipt may be validated for a warranty claim on goods or services subject to the purchase transaction, and the removable storage medium may be an optical card or a smart card, either of which is able to store thousands of e-receipts and other electronic documents related to a commercial transaction, with the integrity of each guaranteed through digital signature, digital certificate, etc.